Optimizing Treatment with TNF Inhibitors in Inflammatory Bowel Disease by Monitoring Drug Levels and Antidrug Antibodies. Issue 8 (August 2016) - Steenholdt, Casper; Bendtzen, Klaus; Brynskov, Jørn; Ainsworth, Mark A.
Abstract : Background: Biological tumor necrosis factor (TNF) inhibitors have revolutionized the treatment of inflammatory bowel disease and redefined treatment goals to include mucosal healing. Clinicians are faced with challenges such as inadequate responses, treatment failures, side effects, and high drug costs. The objective is to review optimization of anti-TNF therapy by use of personalized treatment strategies based on circulating drug levels and antidrug antibodies (Abs), i.e. therapeutic drug monitoring (TDM). Furthermore, to outline TDM-related pitfalls and their prevention. Methods: Literature review. Results: Circulating anti-TNF drug trough level is a marker for the pharmacokinetics (PK) of TNF inhibitors. Because of a number of factors, including antidrug antibodies, PK varies between and within patients across time leading to variable clinical outcomes. Differences in intestinal inflammatory phenotype influencing the pharmacodynamic (PD) responses to TNF inhibitors also affect treatment outcomes. As an alternative to handling anti–TNF-treated patients by empiric strategies, TDM identifies underlying PK and PD-related reasons for treatment failure and aids decision making to secure optimal clinical and economic outcomes. Although promising, evidence does not the support use of TDM to counteract treatment failure in quiescent disease. Use of TDM is challenged by methodological biases, difficulties related to differentiation between PK and PD problems, and temporal biases due to lack of chronology between changes in PK versus symptomatic and objective disease activity manifestations. Biases can be accommodated by knowledgeable interpretation of results obtained by validated assays with clinically established thresholds, and by repeated assessments over time using complimentary techniques. Conclusions: TDM-guided anti-TNF therapy at treatment failure has been brought from bench to bedside.